Pelatihan Penulisan Penelitian Tindakan (Classroom Action Research) Bagi Guru BK di MGBK Blitar Raya - Devy Probowati; Ella Faridati Zen; Widya Multisari (Abdimas Pedagogi: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Abstract: The guidance and counseling teacher or counselor has the role and function of providing guidance and counseling services to all students. Guidance and Guidance Teachers are expected to be able to provide optimal guidance and counseling services, so that to make this happen, Guidance and Guidance Teachers are required to always improve their competence and develop their professionalism. The professional quality of guidance and counseling teachers still varies. The aim of this community service is to improve the research competence of guidance and counseling teachers through classroom action research training at MGBK Blitar Raya. The implementation methods used in community service are online synchronous and asynchronous. This was due to the Covid-19 pandemic which caused this activity to be carried out online. The results of the implementation of the service were obtained based on a process evaluation which showed that 80% of the guidance and counseling teachers followed the presentation of the material provided well. Abstrak: Guru BK diharapkan dapat memberikan layanan BK secara optimal, sehingga untuk mewujudkan hal tersebut guru BK dituntut untuk selalu meningkatkan kompetensi dan mengembangkan keprofesionalannya. Kualitas profesional guru BK ternyata masih beragam. Tujuan pengabdian kepada masyarakat ini adalah untuk meningkatkan kompetensi penelitian guru BK melalui pelatihan classroom action research di MGBK Blitar Raya. Metode pelaksanaan yang digunakan dalam pengabdian kepada masyarakat adalah daring sinkronus dan asinkronus. Hal ini dilatar belakangi karena adanya pandemi covid-19 yang menyebabkan kegiatan ini dilaksanakan secara daring. Hasil pelaksanaan pengabdian diperoleh berdasarkan evaluasi proses yang menunjukkan 80% guru BK mengikuti dengan baik pemaparan materi yang diberikan.